Psychologie práce a organizace 2019 - Procházka, Jakub; Kratochvíl, Tomáš; Vaculík, Martin (Masaryk University Press, 2019)
Title in English: Work and Organisational Psychology 2019 "The 18th International Conference on Work and Organisational Psychology 2019 took place in Brno, at Masaryk University on 22-23 May 2019. Over 130 participants and guests watched and listened to 64 presentations from academics and practitioners from 10 different countries. The contributions covered various areas of work and organisation psychology and related fields. Most represented were psychometric contributions focused on methods used to measure work-psychology constructs, contributions focused on work psychology in the context of educational institutions, and contributions devoted to the application of knowledge of occupational psychology in organisations. Applied psychological disciplines were also significantly represented. This book presents 24 selected studies that were given in the form of a lecture or a poster at the conference and then positively reviewed by two reviewers. We would like to thank our colleagues from Charles University, Palacký University in Olomouc, Tomas Bata University in Zlín, Masaryk University, Comenius University in Bratislava, Constantine the Philosopher University in Nitra, P. J. Šafárik University in Košice and the Slovak Academy of Sciences for helping with the organisation of the conference and for cooperation in the review process. We wish that readers will find interesting information and inspiration for their own praxis. This was a jubilee conference celebrating 20 years since the first Conference on Work and Organisational Psychology, which took place in Slovakia. Therefore, we wish for the conference further interesting contributions, stimulating meetings and continued cooperation over the next 20 years."